2005
DOI: 10.1063/1.2133929
|View full text |Cite
|
Sign up to set email alerts
|

Josephson effect in MgB2∕Pd∕Fe∕Nb Josephson junctions

Abstract: MgB 2 ∕ Pd ∕ Fe ∕ Nb Josephson junctions were fabricated and characterized. The junctions exhibited the Josephson effect. A supercurrent was observed across the magnetically active layer formed at the Pd and Fe interface and also across the magnetic metal Fe itself. Shapiro steps and fractional Shapiro steps were observed when microwave fields were applied to the junctions. Modulation of the critical currents of the junctions was observed when an external magnetic field was applied in the plane of the junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Technologies to produce high quality superconducting thin films and Josephson junctions are prerequisites for such purpose. To this end, various types of Josephson elements have been developed [2]- [14]. Among those are point contact junctions by Zhang et al [2], nanobridges by Brinkmann et al [3], ion damaged weak links by Burnell et al [4] and also by Cybart et al [5], and thin film multilayer junctions [6]- [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies to produce high quality superconducting thin films and Josephson junctions are prerequisites for such purpose. To this end, various types of Josephson elements have been developed [2]- [14]. Among those are point contact junctions by Zhang et al [2], nanobridges by Brinkmann et al [3], ion damaged weak links by Burnell et al [4] and also by Cybart et al [5], and thin film multilayer junctions [6]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shimakage [12] reported all junctions with an AlN barrier layer. Kye et al reported a proximity junction with Ag as the barrier [13] and Malisa fabricated junctions with a Pd/Fe ferromagnetic barrier [14].…”
Section: Introductionmentioning
confidence: 99%